Histologische Diagnostik bei Spenderlebern - Schleicher, Christina; Kreipe, Hans H.; Flechtenmacher, Christa (Der Chirurg, 2019)
BackgroundThe indications, implementation and reporting of liver biopsies for deceased organ donation are not mandatory or regulated. Reliable data on outcome quality and prognostic relevance are therefore not available. Defined standards are thus required to enable meaningful studies and to ensure high data quality of a national transplantation registry.ObjectivePresentation of a synopsis of available studies and literature-based recommendations.Results and conclusionAgainst the background of an organ shortage and a growing number of older donors, pretransplantation liver histology is of significant relevance to guide clinical decision making. With the joint recommendations of the German Transplantation Society (DTG), the German Society of Pathology (DGP) and the German Organ Transplantation Foundation (DSO) standardized procedures are defined for the first time.